2011
DOI: 10.4236/ajps.2011.23051
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Influence of Ozone in Tomato Seed Dormancy Alleviation

Abstract: The study was made on the role of ozone (O 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Alternatively, it could be that ozone generates short-lived species inside the seed, which may be recognized as a signal for germination since the accumulation of ROS and peroxidation products is linked with seed dormancy alleviation [144]. As Sudhakar et al [157] pointed out, the production of hydrogen peroxide is observed in the early imbibition period of tomato seeds and nitric oxide, hydroxyl radicals and superoxide radicals accumulate during seed germination in different species. For this reason, many scientists speculate that H 2 O 2 and NO are the reason for the observed effects using plasma treatments, whether or not it is the short-lived species such as superoxide, hydroxyl and NO that are eventually converted into H 2 O 2 [55].…”
Section: Ros Entry and Involvement In Seed Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it could be that ozone generates short-lived species inside the seed, which may be recognized as a signal for germination since the accumulation of ROS and peroxidation products is linked with seed dormancy alleviation [144]. As Sudhakar et al [157] pointed out, the production of hydrogen peroxide is observed in the early imbibition period of tomato seeds and nitric oxide, hydroxyl radicals and superoxide radicals accumulate during seed germination in different species. For this reason, many scientists speculate that H 2 O 2 and NO are the reason for the observed effects using plasma treatments, whether or not it is the short-lived species such as superoxide, hydroxyl and NO that are eventually converted into H 2 O 2 [55].…”
Section: Ros Entry and Involvement In Seed Developmentmentioning
confidence: 99%
“…Ji et al [168,169] also observed an increase in GA in spinach seeds but did not measure any other hormones. The increase in GA may be the result of plasmaderived ozone [157] although it is often speculated that it is specifically auxin and cytokinins that are affected, which are hormones that increase and stimulate cell division, proliferation and elongation. Perez Pizá et al [170] showed that with plasma treatment, there was a decrease in ABA and increase in IAA, a hormone which increases growth by regulating enzyme activity.…”
Section: Hormonesmentioning
confidence: 99%
“…The change of wetting properties and structure of the coat increases the water uptake, the permeability of nutrients, or it accelerates the root formation . Furthermore, several effects on plant hormones, enzymes such as catalase, proteins, soluble sugar, and antioxidants are possible . The plasma treatment is not only affecting the seeds, but it also affects the environmental conditions, such as the pH‐value or the introduction of nitrate and nitrous species into the surrounding water.…”
Section: Plasma Technology For and In Agriculturementioning
confidence: 99%
“…The effects of seeds exposure to ozone have been studied and a method that benefits the seed germination has been patented by Yvin and Coste (1995), and the another one by Klaptchuk (2004) to sterilize the seeds and degrade residual herbicides with use of ozone. It has been found that exposure to ozone favors the acceleration of tomato seed germination by breaking dormancy (Sudhakar et al, 2011); however, according to Wu et al (2006) the prolonged exposure to gas can reduce the germination of wheat seeds. Studies by Violleau et al (2008) have suggested that long periods of ozonization may be harmful for the quality of the seeds; however, which would a long period be has not been specified.…”
Section: Introductionmentioning
confidence: 99%